A kind of coal gangue-based cementitious material and preparation method thereof

Through ball milling and activation treatment of coal gangue and steel slag powder, combined with mechanical stirring and alkaline exciter, a highly active ingredient coal gangue-steel slag activation material was prepared, which solved the problems of high energy consumption and pollution in the existing technology and significantly improved the early strength of coal gangue-based gelling materials.

CN117209174BActive Publication Date: 2025-03-25TONGLING TONGGUAN JIANAN NEW ENVIRONMENTAL PROTECTION BUILDING MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311128336.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-25
Estimated Expiration
2043-09-04

AI Technical Summary

Technical Problem

The existing preparation methods for coal gangue-based gelling materials have problems of high energy consumption and pollutant gas emissions, and the early intensity is insufficient.

Method used

The coal gangue and steel slag powder are pretreated by ball milling, and the activated gangue-steel slag powder slurry is added to form an activated gangue-steel slag powder slurry. Combined with the effects of mechanical stirring and alkaline excitants, a highly active ingredient and evenly dispersed gangue-steel slag activation material is prepared to form a gel network framework to improve the early strength of the material.

Benefits of technology

The preparation of gelling materials with low energy consumption and pollutant-free gas emissions has been achieved, which has significantly improved the early strength of coal gangue-based gelling materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004429198670000081
    Figure BDA0004429198670000081
  • Figure BDA0004429198670000091
    Figure BDA0004429198670000091
  • Figure BDA0004429198670000092
    Figure BDA0004429198670000092
Patent Text Reader

Abstract

The present invention relates to a gangue-based cementitious material and a preparation method thereof. In a first aspect, the present application relates to a gangue-based cementitious material, comprising the following components by weight: 1-60 parts of gangue, 100-150 parts of mineral powder, 5-10 parts of steel slag powder, 5-20 parts of desulfurized ash, 10-30 parts of quicklime, 10-15 parts of alkaline activator and 3-18 parts of activator. The present invention activates the steel slag powder and gangue through an activator and ball milling to form a gangue-steel slag activated material with high active ingredients and uniform dispersion, so as to form a gel network skeleton, and other components cooperate with the alkaline activator to fill the skeleton, thereby improving the early strength of the gel material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gel materials, and in particular to a gangue-based gelling material and a preparation method thereof. Background Art

[0002] At present, using coal gangue as the main raw material to replace cement to prepare cementitious materials and developing low-cost, efficient and environmentally friendly green ecological cementitious materials has always been a research hotspot in the field of environmental protection. The main components of coal gangue are Al2O3 and SiO2, which are similar to building materials. Therefore, how to use coal gangue to prepare cementitious materials is an important way to realize the consumption and application of coal gangue.

[0003] As for the current process of preparing gel materials using coal gangue, the Chinese patent with the announcement number CN113233797B discloses a coal gangue-based gelling material and a preparation method thereof, and specifically discloses the use of high-temperature calcination to increase the activity of coal gangue, thereby improving the early strength of the gel material. However, this preparation method still has the problems of high energy consumption and pollutant gas emissions. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a gangue-based cementitious material and a preparation method thereof. The specific technical scheme is as follows:

[0005] On the one hand, the present application provides a gangue-based cementitious material, comprising the following components by weight: 1-60 parts of gangue, 100-150 parts of mineral powder, 5-10 parts of steel slag powder, 5-20 parts of desulfurization ash, 10-30 parts of quicklime, 10-15 parts of alkali activator and 3-18 parts of activator.

[0006] Through the above technical solution, the proportion of coal gangue in the gel material can be increased, and a large amount of coal gangue can be consumed, which can effectively reduce costs.

[0007] As an improvement of the above technical solution, the alkaline activator includes one or more of sodium carbonate, potassium carbonate or water glass.

[0008] As an improvement of the above technical solution, the activator includes sodium humate, sodium hydroxide, magnesium hydroxide and triethanolamine, and the ratio of the sodium humate, sodium hydroxide, magnesium hydroxide and triethanolamine is (1-2.5): (0.05-0.3): (0.5-1): (0.5-3).

[0009] Through the above technical scheme, the internal dissociation of coal gangue and steel slag powder can be rapid, the gelling activity of coal gangue and steel slag powder can be enhanced, and a coal gangue-steel slag activated material with high active ingredients and uniform dispersion can be formed to facilitate the formation of a gel network skeleton.

[0010] In a second aspect, the present application provides a method for preparing the gel material, comprising the following steps:

[0011] S1 Pretreatment of coal gangue: ball milling the coal gangue to crush the coarse-grained coal gangue into a predetermined particle size;

[0012] S2 activation treatment: adding an activator and steel slag powder during the ball milling process to obtain an activated coal gangue-steel slag powder slurry;

[0013] S3 composite powder: the activated gangue-steel slag slurry, mineral powder, desulfurization ash and quicklime are mechanically stirred uniformly according to the proportion to obtain a composite powder;

[0014] S4 gel slurry preparation: dry-mix the activator and the composite powder, then pour in a proper amount of water and stir evenly to obtain a gelling material.

[0015] Through the above technical scheme, during the ball milling process, defects can be formed on the surfaces of coal gangue particles and steel slag powder, which can accelerate the dissolution of soluble Al2O3, SiO2 and calcium oxide, facilitate the invasion of external ions, and when combined with an activator, the chemical reaction rate can be accelerated, so that a large number of Si-O, Al-O and Ca-O bonds are broken to achieve the purpose of activation. When combined with an activator, a coal gangue-steel slag activated material with high active ingredients and uniform dispersion is formed to facilitate the formation of a gel network skeleton. Other ingredients, under the action of the alkaline activator, cooperate with calcium ions to fill the skeleton, thereby improving the strength of the gel material.

[0016] As an improvement of the above technical solution, in the pretreatment of the coal gangue, the ball milling time is 40-60 minutes.

[0017] As an improvement of the above technical solution, in the pretreatment of the coal gangue, the coal gangue is crushed to a particle size of 60 μm to 90 μm.

[0018] As an improvement of the above technical solution, the mechanical stirring and mixing time is 20 to 25 minutes.

[0019] As an improvement of the above technical solution, the activated gangue-steel slag powder slurry is placed in a microwave heating furnace before washing for microwave excitation treatment, and then the activated gangue powder slurry is washed with distilled water for multiple times to remove impurities, and then filtered and dried to obtain activated gangue.

[0020] As an improvement of the above technical solution, the microwave excitation treatment is performed at a power of 650 to 690 W, and the temperature is raised to 400 to 650° C.

[0021] As an improvement of the above technical solution, the microwave excitation treatment is 10-20 minutes.

[0022] Beneficial effects of the present invention:

[0023] 1. The technical solution provided by the invention activates steel slag powder and coal gangue, and through a specific preparation method, makes them have a higher gelling activity again, thereby forming a uniformly distributed gelling structure network skeleton, thereby improving the early strength of the gel material.

[0024] 2. The preparation method provided by the present invention does not require a high-temperature calcination process, so it has low energy consumption and no pollutant gas emissions. At the same time, by using the preparation method provided by the present invention, the activity of steel slag powder and coal gangue is greatly improved, thereby improving the early strength of the gel material. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0026] The present application designs a gangue-based cementitious material, comprising the following components by weight: 1-60 parts of gangue, 100-150 parts of mineral powder, 5-10 parts of steel slag powder, 5-20 parts of desulfurized ash, 10-30 parts of quicklime, 10-15 parts of alkali activator and 3-18 parts of activator.

[0027] In a second aspect, the present application provides that the gel material is prepared by the following method, comprising the following steps:

[0028] S1 Pretreatment of coal gangue: ball milling the coal gangue to crush the coarse-grained coal gangue into a predetermined particle size;

[0029] S2 activation treatment: adding an activator and steel slag powder during the ball milling process to obtain an activated coal gangue-steel slag powder slurry;

[0030] S3 composite powder: the activated gangue-steel slag slurry, mineral powder, desulfurization ash and quicklime are mechanically stirred uniformly according to the proportion to obtain a composite powder;

[0031] S4 gel slurry preparation: dry-mix the activator and the composite powder, then pour in a proper amount of water and stir evenly to obtain a gelling material.

[0032] The present application grinds coal gangue and steel slag powder so that defects are formed on the surfaces of coal gangue particles and steel slag powder, accelerates the dissolution of soluble Al2O3, SiO2 and calcium oxide, and facilitates the invasion of external ions. When combined with an activator, the chemical reaction rate can be accelerated, so that a large number of Si-O, Al-O and Ca-O bonds are broken to achieve the purpose of activation. Under the joint action of sodium humate, sodium hydroxide, magnesium hydroxide and triethanolamine, the effective components inside the coal gangue and steel slag powder can be quickly dissociated, which is convenient for subsequent hydration reactions to re-aggregate, thereby enhancing the gelling activity of the coal gangue and steel slag powder, forming a coal gangue-steel slag activated material with high active ingredients and uniform dispersion, so as to form a gel network skeleton. Other components fill the gel network skeleton under the coordinated action of the alkaline activator, thereby improving the strength of the gel material.

[0033] At the same time, when activating coal gangue and steel slag, a physical and chemical activation method that assists each other is used, so there is no need for calcination, the high-temperature calcination step is omitted, the process is simplified, the energy consumption is low, and there is no pollutant gas emission. At the same time, compared with the calcination method, the chemical reaction activity of coal gangue or steel slag has been greatly improved.

[0034] Unless otherwise specified, the components involved in the preparation examples and embodiments of this application were purchased from commercially available products.

[0035] Sodium humate: purchased from Jinan Qinghai Chemical Co., Ltd.

[0036] Sodium hydroxide: purchased from Shandong Mingxu Chemical Co., Ltd.;

[0037] Triethanolamine: Tianjin Xinnuowei Chemical Co., Ltd.;

[0038] The ore powder was purchased from Beijing Shougang Co., Ltd. The mass percentages of the main chemical components of the slag powder are: CaO: 37.7%, SiO2: 20.04%, Fe2O3: 12.57%, MgO: 9.45%, Al2O3: 8.15%, SO3: 0.69%, MnO2: 0.78%, and others: 10.62%.

[0039] The steel slag powder was purchased from Beijing Shougang Co., Ltd. The mass percentages of the main chemical components of the steel slag powder are: CaO: 34.15%, SiO2: 41.2%, Fe2O3: 13.66%, MgO: 8.47%, Al2O3: 0.84%, MnO2: 1.11%, and others: 0.57%.

[0040] Desulfurization ash was purchased from Beijing Shougang Co., Ltd. The main chemical components of the desulfurization ash were as follows by mass percentage: CaO 52.40%, SO3 24.96%, MgO 1.23%, SiO2 0.36%, Fe2O3 0.35%, and Al2O3 0.11%.

[0041] Quicklime was purchased from Shang'an Dong Biyun Lime Powder Factory in Jingxing County. The mass percentages of the main chemical components of the quicklime were: CaO: 90.25%, and others: 9.75%.

[0042] Gangue: The mass percentages of the main chemical components of the gangue are: SiO2 40%, Al2O3 40%, CaO 1.2%, Fe2O3 1.5%, MgO 1.0%, TiO2 0.53.0%, K2O 0.5-3.0%, Na2O 0.5-3.0%, and other elements 0.1-1.0%.

[0043] Preparation Examples 1-3 are used to prepare different activator solutions.

[0044] Preparation Example 1

[0045] 1 kg of sodium humate, 1.2 kg of sodium hydroxide, 0.5 kg of magnesium hydroxide and 0.5 kg of triethanolamine were added to a beaker in sequence, and then an appropriate amount of water was added to prepare an activator solution.

[0046] Preparation Example 2

[0047] 2.5 kg of sodium humate, 0.8 kg of sodium hydroxide, 1 kg of magnesium hydroxide and 3 kg of triethanolamine were added to a beaker in sequence, and then an appropriate amount of water was added to prepare an activator solution.

[0048] Preparation Example 3

[0049] 1.7 kg of sodium humate, 1.5 kg of sodium hydroxide, 0.8 kg of magnesium hydroxide and 2 kg of triethanolamine were added to a beaker in sequence, and then an appropriate amount of water was added to prepare an activator solution. Specific embodiments

[0051] Example 1

[0052] The gangue gel material of this embodiment includes the following components by weight: 1 kg of gangue, 125 kg of mineral powder, 5 kg of steel slag powder, 5 kg of desulfurized ash, 10 kg of quicklime, 10 kg of stimulant and 3 kg of activator.

[0053] The gel material of the above embodiment is prepared by the following method, comprising the following steps:

[0054] S1. Pretreatment of coal gangue: ball milling the coal gangue to crush the coarse-grained coal gangue into a predetermined particle size, and the ball milling time is 50 minutes;

[0055] S2 Activation Treatment: During the ball milling process, the activator prepared in Preparation Example 1 and steel slag powder are added to obtain an activated coal gangue-steel slag powder slurry.

[0056] S3 composite powder; the activated gangue-slag powder slurry, mineral powder, desulfurized ash and quicklime are mechanically stirred uniformly according to the proportion to obtain a composite powder, and the mechanical stirring and mixing time is 20 minutes;

[0057] S4 gel slurry preparation: dry-mix water glass and composite powder, then pour in a proper amount of water and stir evenly to obtain a gelling material.

[0058] Example 2

[0059] The gangue gel material of this embodiment includes the following components by weight: 45 kg of gangue, 100 kg of mineral powder, 1 kg of steel slag powder, 12 kg of desulfurized ash, 30 kg of quicklime, 13 kg of stimulant and 10 kg of activator.

[0060] The gel material of the above embodiment is prepared by the following method, comprising the following steps:

[0061] The gangue gel material of this embodiment includes the following components by weight: 1 kg of gangue, 125 kg of mineral powder, 5 kg of steel slag powder, 5 kg of desulfurized ash, 10 kg of quicklime, 10 kg of stimulant and 3 kg of activator.

[0062] The gel material of the above embodiment is prepared by the following method, comprising the following steps:

[0063] S1. Pretreatment of coal gangue: ball milling the coal gangue to crush the coarse-grained coal gangue into a predetermined particle size, and the ball milling time is 40 minutes;

[0064] S2 Activation Treatment: During the ball milling process, the activator prepared in Preparation Example 2 and steel slag powder are added to obtain an activated coal gangue-steel slag powder slurry.

[0065] S3 composite powder; the activated gangue-slag slurry, mineral powder, desulfurized ash and quicklime are mechanically stirred evenly according to the proportion to obtain a composite powder, and the mechanical stirring and mixing time is 22 minutes;

[0066] S4 gel slurry preparation: dry-mix sodium carbonate and composite powder, then pour in appropriate amount of water and stir evenly to obtain a gelling material.

[0067] Example 3

[0068] The gangue gel material of this embodiment includes the following components by weight: 60 kg of gangue, 150 kg of mineral powder, 8 kg of steel slag powder, 20 kg of desulfurized ash, 20 kg of quicklime, 15 kg of stimulant and 18 kg of activator.

[0069] The gel material of the above embodiment is prepared by the following method, comprising the following steps:

[0070] S1. Pretreatment of coal gangue: ball milling the coal gangue to crush the coarse-grained coal gangue into a predetermined particle size, and the ball milling time is 60 minutes;

[0071] S2 Activation Treatment: During the ball milling process, the activator prepared in Preparation Example 3 and steel slag powder are added to obtain an activated coal gangue-steel slag powder slurry.

[0072] S3 composite powder; the activated gangue-steel slag slurry, mineral powder, desulfurization ash and quicklime are mechanically stirred evenly according to the proportion to obtain a composite powder; the mechanical stirring and mixing time is 25 minutes.

[0073] S4 gel slurry preparation: potassium carbonate and composite powder are dry-mixed, then poured into a proper amount of water and stirred evenly to obtain a gelling material.

[0074] Comparative Example 1

[0075] The difference from Example 2 is that the coal gangue gel material of this example includes the following components by weight: 130 kg of mineral powder, 3 kg of steel slag powder, 2 kg of desulfurized ash, 35 kg of quicklime, 8 kg of stimulant and 1 kg of activator.

[0076] Comparative Example 2

[0077] The difference from Example 2 is that the coal gangue gel material of this example includes the following components by weight: 65 kg of coal gangue, 95 kg of mineral powder, 15 kg of steel slag powder, 25 kg of desulfurization ash, 5 kg of quicklime, 18 kg of stimulant and 20 kg of activator.

[0078] The gel materials prepared in Examples 1-3 and Comparative Examples 1-2 were used to perform early strength tests. The test results are shown in Table 1.

[0079]

[0080]

[0081] Table 1

[0082] It can be seen from the test results of Examples 1-3 and Comparative Examples 1 and 2 that the formula and method of the present application significantly improve the early strength of the gel material.

[0083] The ratio of the coal gangue and the activator in the present application has a synergistic effect. The two can further improve the early strength of the gel material with appropriate addition amounts and ratios. The synergistic effect of the coal gangue and the activator is verified by Examples 4-8 below. The specific ratio of the coal gangue and the activator is shown in Table 2;

[0084]

[0085] Table 2

[0086] The early compressive strength of the gel materials prepared in Examples 4-7 was tested to verify the synergistic effect of the ratio of the coal gangue and the activator in the present application. The specific results are shown in Table 3.

[0087]

[0088]

[0089] Table 3

[0090] The above performance tests, among which, through Examples 4-5 in combination with Example 2, it can be seen that when the ratio of coal gangue to activator is 4.5:(0.5-1.5), when the ratio of activator is gradually increased, the ratio of activator is between 0.5-1.5, and the early strength of the prepared gel material reaches a peak.

[0091] Among them, through Examples 6-7 in combination with Example 2, it can be seen that when the ratio of gangue to activator is 1:(4-5), the ratio of gangue is gradually increased. When the ratio of gangue added is between 4-5, the compressive strength of the gel material reaches a peak.

[0092] The inventors found that when the particle size of the coal gangue is too large or too small, it affects the early compressive strength. The inventors speculate that this is because the coal gangue particle size is too small, and when forming a three-dimensional network structure, the too small coal gangue cannot effectively fill the gaps; and the coal gangue particle size is too large, which also reduces the contact area of ​​the activator, making it difficult for the internal chemical bonds of the coal gangue to break, and thus difficult to be activated.

[0093] The particle size of coal gangue is verified by Examples 8-10 below.

[0094] Example 8

[0095] This embodiment adopts the same formula and preparation method as that of Example 5 of the present application, the difference being the particle size of the coal gangue. The particle size of the coal gangue in this embodiment is selected to be 40-50 μm.

[0096] Example 9

[0097] This embodiment adopts the same formula and preparation method as that of Example 5 of the present application, the difference being the particle size of the coal gangue. The particle size of the coal gangue in this embodiment is selected to be 60-90 μm.

[0098] Example 10

[0099] This embodiment adopts exactly the same proportion and preparation method as Example 5 of the present application, the difference lies in the particle size of the coal gangue. The particle size of the coal gangue selected in this embodiment is 95-110 μm.

[0100] The early compressive strength of the gel materials prepared in Examples 8-10 was tested to verify the effect of the particle size of the coal gangue in the gel material. The specific results are shown in Table 4.

[0101]

[0102] Table 4

[0103] It can be seen from the data in Table 4 that for coal gangue in the range of 40-110 μm, as the particle size increases, the compressive strength of the gel material shows a trend of first increasing and then decreasing.

[0104] The inventors also found that the coal gangue prepared by the physical and chemical activation method can further improve the early strength of the gel material and have an impact on the prepared gel strength. The inventors speculate that by adding an activator during the ball milling process, the coal gangue can form a coal gangue activated material with high active ingredients and uniform dispersion during the ball milling process. As a cementitious material for cement, it can well improve the compressive strength. The coal gangue activation method is verified by Examples 11-12 below.

[0105] Embodiment 11

[0106] This embodiment adopts exactly the same ratio as that of Example 9 of the present application, the difference being the activation treatment method of the coal gangue. In this embodiment, the coal gangue powder obtained by ball milling is activated by calcination. The specific operation method is: the calcination temperature is 600° C., and the calcination time is 5 hours.

[0107] Example 12

[0108] This embodiment adopts the same formula as that of Embodiment 9 of the present application, the difference being the activation treatment method of the coal gangue. In this embodiment, the coal gangue powder obtained by ball milling is activated by calcination. The specific operation method is: the calcination temperature is 900° C., and the calcination time is 6 hours.

[0109] The early compressive strength of the gel material prepared in Examples 11-12 was tested to verify the influence of the activation method of the gangue. The specific results are shown in Table 5.

[0110]

[0111] Table 5

[0112] Through Examples 11-12 in conjunction with Example 9, it can be seen that the chemical reaction activity of coal gangue is greatly improved through the physical and chemical activation method, thereby improving the early strength of the gel material.

[0113] The inventors also found that after chemical activation, the activity of coal gangue and steel slag can be further improved by microwave excitation treatment.

[0114] Embodiment 13

[0115] This embodiment adopts exactly the same ratio as Example 9 of the present application, except that the activated coal gangue-steel slag powder slurry is placed in a microwave heating furnace before washing, and the temperature is raised to 500°C at a power of 650 W for microwave excitation treatment for 10 minutes, and then the activated coal gangue powder slurry is washed multiple times with distilled water to remove impurities, and then filtered and dried to obtain activated coal gangue.

[0116] Embodiment 14

[0117] This embodiment adopts exactly the same ratio as Example 9 of the present application, except that the activated coal gangue-steel slag powder slurry is placed in a microwave heating furnace before washing, and the temperature is raised to 400°C at a power of 690 W for microwave excitation treatment for 15 minutes, and then the activated coal gangue powder slurry is washed with distilled water for multiple times to remove impurities, and then filtered and dried to obtain activated coal gangue.

[0118] Embodiment 15

[0119] This embodiment adopts exactly the same ratio as Example 9 of the present application, except that the activated coal gangue-steel slag powder slurry is placed in a microwave heating furnace before washing, and the temperature is raised to 650°C at a power of 670 W for microwave excitation treatment for 15 minutes, and then the activated coal gangue powder slurry is washed with distilled water for multiple times to remove impurities, and then filtered and dried to obtain activated coal gangue.

[0120] The early compressive strength of the gel materials prepared in Examples 13-15 was tested to verify the influence of the activation method of the coal gangue. The specific results are shown in Table 6.

[0121]

[0122] Table 6

[0123] Through Examples 13-15 in conjunction with Example 9, it can be seen that after chemical activation, microwave excitation treatment can further improve the early compressive strength of the gel material.

[0124] Performance Test:

[0125] Examples 1-12 and Comparative Examples 1-2 were made into 7cm x 7cm x 7cm cubic compression test blocks, and cured under the new cement mortar strength test standard GBT17671. According to GB / T17671-1999 "Cement mortar strength test method (ISO method)", the compressive strengths of the blocks were measured at 3 days, 7 days, and 28 days, respectively.

[0126] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A gangue-based cementitious material, characterized in that: The invention comprises the following components by weight: 1-60 parts of coal gangue, 100-150 parts of mineral powder, 5-10 parts of steel slag powder, 5-20 parts of desulfurized ash, 10-30 parts of quicklime, 10-15 parts of alkali activator and 3-18 parts of activator; The activator comprises sodium humate, sodium hydroxide, magnesium hydroxide and triethanolamine, and the ratio of the sodium humate, sodium hydroxide, magnesium hydroxide and triethanolamine is (1-2.5): (0.05-0.3): (0.5-1): (0.5-3).

2. The gangue-based cementitious material according to claim 1, characterized in that: The alkaline activator includes one or more of sodium carbonate, potassium carbonate or water glass.

3. A method for preparing a gelling material as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: S1 Pretreatment of coal gangue: ball milling the coal gangue to crush the coarse-grained coal gangue to a predetermined particle size; S2 activation treatment: adding an activator and steel slag powder during the ball milling process to obtain an activated coal gangue-steel slag powder slurry; S3 composite powder: the activated gangue-steel slag slurry, mineral powder, desulfurization ash and quicklime are mechanically stirred uniformly according to the proportion to obtain a composite powder; S4 Preparation of gelling slurry: After dry-mixing the activator and the composite powder, pour in a proper amount of water and stir evenly to obtain the gelling material.

4. The method for preparing a gelling material according to claim 3, characterized in that: In the coal gangue pretreatment, the ball milling time is 40-60 minutes.

5. The method for preparing a gelling material according to claim 3, characterized in that: In the pretreatment of the coal gangue, the coal gangue is crushed to a particle size of 60 μm to 90 μm.

6. The method for preparing the gelling material according to claim 3, characterized in that: The mechanical stirring and mixing time is 20 to 25 minutes.

7. The method for preparing a gelling material according to claim 3, characterized in that: The activated gangue-steel slag powder slurry is placed in a microwave heating furnace for microwave excitation treatment, and then the activated gangue powder slurry is washed with distilled water for multiple times to remove impurities, and then filtered and dried to obtain activated gangue.

8. The method for preparing a gelling material according to claim 7, characterized in that: The microwave excitation treatment is performed at a power of 650-690W to raise the temperature to 400-650°C.

9. The method for preparing a gelling material according to claim 8, characterized in that: The microwave excitation treatment is performed for 10-20 min.

Citation Information

Patent Citations

  • A coal gangue-based cementitious material and its preparation method

    CN113233797B

  • Chemical preparation method of active coal gangue

    CN106746822A

  • Cementing material with coal gangue as raw material and preparation method of cementing material

    CN109485278A